Motivasi Dan Mekanisme Pertahanan Diri Tokoh Timun Dalam Novel Timun Jelita Karya Raditya Dika: Analisis Psikologi Sastra - Muhammad Andy Arifin; Moh. Ahsan Shohifur Rizal (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This research examines the psychological dynamics of the main character Timun in the novel Timun Jelita by Raditya Dika through the lens of literary psychology. The main problems faced by Timun, a 40-year-old accountant, include identity crisis, existential anxiety in facing technological developments, and past trauma in music. Through Sigmund Freud's psychoanalytic approach, this study aims to reveal how the personality structure consisting of id, ego, and superego contributes to driving the character's behavior. The imbalance in the interaction of these three elements gives rise to anxiety, which then activates the character's unconscious motivation to maintain his psychic integrity. As an adaptive response to emotional pressure, Timun's ego activates various forms of defense mechanisms, including denial, regression, projection, rationalization, reaction formation, and sublimation. This research uses a qualitative descriptive method with data collection techniques in the form of reading and note-taking. The research data are in the form of dialogues, narrations, monologues, and behavioral descriptions of the main character in the novel. The results show that the integration of motivational drives and ego defense mechanisms successfully helps Timun reduce his emotional anxiety and guides him toward a more realistic phase of self-acceptance amid the demands of modern life.